Plasticity of photosynthetic processes and the accumulation of secondary metabolites in plants in response to monochromatic light environments: A review - Landi, Marco; Zivcak, Marek; Sytar, Oksana; Brestic, Marian; Allakhverdiev, Suleyman I (Biochimica et biophysica acta. Bioenergetics, 2020)
Light spectra significantly influence plant metabolism, growth and development. Here, we review the effects of monochromatic blue, red and green light compared to those of multispectral light sources on the morpho-anatomical, photosynthetic and molecular traits of herbaceous plants. Emphasis is given to the effect of light spectra on the accumulation of secondary metabolites, which are important bioactive phytochemicals that determine the nutritional quality of vegetables. Overall, blue light may promote the accumulation of phenylpropanoid-based compounds without substantially affecting plant morpho-anatomical traits compared to the effects of white light. Red light, conversely, strongly alters plant morphology and physiology compared to that under white light without showing a consistent positive effect on secondary metabolism. Due to species-specific effects and the small shifts in the spectral band within the same color that can substantially affect plant growth and metabolism, it is conceivable that monochromatic light significantly affects not only plant photosynthetic performance but also the "quality" of plants by modulating the biosynthesis of photoprotective compounds.
Keywords: Photosynthesis; rostliny; listy rostlin; světlo; Plants; Chlorophyll; chlorofyl; Light; fotosyntéza; Plant Leaves